Hypertension and Its Impact on Stroke Recovery: From a Vascular to a Parenchymal Overview - Benjamin Maïer; Nathalie Kubis (Neural Plasticity)
Hypertension is the first modifiable vascular risk factor accounting for 10.4 million deaths worldwide; it is strongly and independently associated with the risk of stroke and is related to worse prognosis. In addition, hypertension seems to be a key player in the implementation of vascular cognitive impairment. Long-term hypertension, complicated or not by the occurrence of ischemic stroke, is often reviewed on its vascular side, and parenchymal consequences are put aside. Here, we sought to review the impact of isolated hypertension or hypertension associated to stroke on brain atrophy, neuron connectivity and neurogenesis, and phenotype modification of microglia and astrocytes. Finally, we discuss the impact of antihypertensive therapies on cell responses to hypertension and functional recovery. This attractive topic remains a focus of continued investigation and stresses the relevance of including this vascular risk factor in preclinical investigations of stroke outcome.